Blistering of W-Ta composites at different irradiation energies - Mateus, R. (2014)
Pure tungsten and tantalum plates and tungsten-tantalum composites produced via mechanical alloying and spark plasma sintering were bombarded with He+ and D+ energetic ion beams and deuterium plasmas. The aim of this experiment is to study the effects caused by individual helium and deuterium exposures and to evidence that the modifications induced in the composites at different irradiation energies could be followed by irradiating the pristine constituent elements under the same experimental conditions, which is relevant considering the development of tailored composites for fusion applications. Higher D retentions, especially in tungsten, and superficial blistering are observed in both components after helium exposure. The blistering is magnified in the tantalum phase of composites due to its higher ductility and to water vapour production under deuterium irradiation. At lower irradiation energies the induced effects are minor. After plasma exposure, the presence of tantalum does not increase the D content in the composites. (C) 2013 Elsevier B.V. All rights reserved.